Normal values of distal radioulnar translation assessed by three-dimensional C-arm scans: a cadaveric study. (June 2019) - Swartman, Benedict; Benner, Laura; Grechenig, Stephan; Franke, Jochen; Grützner, Paul A.; Schnetzke, Marc
We investigated whether mobile C-arm cone beam computer tomography (CBCT) could be used to measure radioulnar translation. The study was conducted on 31 Thiel-fixed intact cadaver arms. Three-dimensional scans of each wrist were carried out in pronation and supination. Four established measurement methods were used (radioulnar line, subluxation ratio, epicentre and radioulnar ratio methods) to measure radioulnar translation. The intraclass correlation coefficient for inter-observer and intra-observer reliability were excellent in three of four methods (>0.94). The reference ranges for physiological radioulnar translation were between −30% and 91% (radioulnar line method), −32% and 87% (subluxation ratio method), −40% and 23% (epicentre method), and 2% and 73% (radioulnar ratio method). Our results indicate that radioulnar translation in the distal radioulnar joint can be determined reliably using mobile C-arm CBCT. The normal values provide a basis for further experimental and clinical studies.